PENDEKATAN SOSIOLOGI SEJARAH PADA KOMODITAS GARAM RAKYAT: DARI EKSPOR MENJADI IMPOR - Rochwulaningsih, Yety (History Department, Semarang State University and Historian Society of Indonesia, 2012)
This paper studies the contradictory phenomenon of peoples salt business sector in Indonesia. Observation method, random sampling of statistical data, in-depth interview, and historical method were used to examine this issue. The results showed that indeed there has been a very significant change in peopleÃ¢â¬â¢s salt business in Indonesia which was originally an export commodity, became an import commodity. It was mainly influenced by the governmentÃ¢â¬â¢s regulatory policies. In the Dutch colonial period, the government took the monopolistic policy to make salt as an export commodity by applying a salt monopoly ordinance. The policy was valid until Indonesia gained its independence and was abolished through the Law no. 13/1959, and there was no further policy that protects peoples salt business. Thus there was a tendency for an administrational shift from monopolistic to privatization and liberalization which was characterized by the deterioration of governmentÃ¢â¬â¢s role. Key words: salt, governmentÃ¢â¬â¢s policy, monopoly, liberalization. ÃÂ Artikel ini mendeskripsikan fenomena yang kontradiktif pada sektor usaha garam rakyat di Indonesia. Untuk mengkaji masalah ini digunakan metode observasi, random sampling data statistik, indepth interview, dan metode sejarah. Hasil penelitian menunjukkan, bahwa memang benar telah terjadi perubahan sangat signifikan pada usaha garam rakyat di Indonesia, yang semula merupakan komoditas ekspor menjadi impor. Hal ini utamanya dipengaruhi oleh regulasi kebijakan pemerintah. Pada masa kolonial Belanda, untuk menjadikan garam sebagai komoditas ekspor ditempuh kebijakan monopoli garam oleh pemerintah dengan menerapkan ordonansi monopoli garam (Zoutmonopolie-Ordonnantie). Ketika Indonesia merdeka kebijakan itu masih berlaku dan baru dihapus melalui UU No. 13/1959, dan selanjutnya tidak pernah ada kebijakan yang memproteksi usaha garam rakyat. Dengan demikian terdapat kecenderungan terjadi pergeseran kebijakan dari monopoli ke arah liberalisasi, yang ditandai semakin kecilnya peran pemerintah dan dominasi swasta. Kata kunci: garam, kebijakan pemerintah, monopoli, liberalisasi. ÃÂ